New Developments in Exosomal lncRNAs in Cardiovascular Diseases - Yuan, Zhu; Huang, Weiqiang (Frontiers in Cardiovascular Medicine, 2021)
LncRNAs are noncoding RNAs with lengths greater than 200 nt that are involved in the occurrence and development of cardiovascular diseases (CVDs). Exosomes are secreted and produced by various cell types. Exosome contents include various ncRNAs, proteins and lipids. Exosomes are also important mediators of intercellular communication. The proportion of lncRNAs in exosomes is low, but increasing evidence shows that exosomal lncRNAs play important roles in CVDs. We focused on the research progress on exosomal lncRNAs in atherosclerosis, myocardial infarction, myocardial ischemia-reperfusion injury, cardiac angiogenesis, cardiac aging, rheumatic heart disease, and chronic kidney disease combined with CVD. The potential diagnostic and therapeutic effects of exosomal lncRNAs in CVDs are summarized based on preclinical studies of animal and cell models, as well as circulating exosomes in clinical patients. Finally, the potential of engineering exosomes and exosomal proteomics in CVD applications are discussed.